To All Members - Irvin Mayers (Canadian Respiratory Journal)
Two years ago, after much debate and discussion, the board of the Canadian Thoracic Society (CTS) decided to combine our annual meeting with the annual meeting of the American College of Chest Physicians (ACCP). There has been ongoing discussion as to whether this was the best course of action. Many members have raised the question of why we did not meet with the American Thoracic Society (ATS) or why we did not develop a stand-alone, made-in-Canada meeting.